Trends and determinants of obesity among ever-married women aged 15–49 in India: insights from National Family Health Surveys (NFHS 1998–2021) - Aditya Singh; Sadanand Karun; Mahashweta Chakrabarty; Rakesh Chandra; Shivani Singh (BMC Public Health)
Abstract Background Obesity has emerged as a significant public health concern in India, particularly among ever-married women of reproductive age (EMWRA). This study analyses trends in obesity among EMWRA across India and its states from 1998 to 2021 and explores the factors contributing to obesity in this group. Methods Data from four National Family Health Survey (NFHS) rounds, spanning 1998-99 to 2019-21, were pooled to create a dataset of 1,117,433 participants. We analysed obesity trends in India and its states and assessed β- and σ-convergence in obesity rates during this period. Additionally, we examined changes in socioeconomic differentials in obesity over this period. Binary logistic regression was used to explore the association of obesity with socioeconomic, demographic, and temporal factors. Results Over the study period, obesity among ever-married women of reproductive age (EMWRA) in India has shown a startling increase, tripling from 5.1% (95% CI: 4.7–5.5) in 1998-99 to 15.7% (15.4–15.9) in 2019-21. While obesity rates have surged across all states, the degree of increase varies significantly (ranging from 22.9% points in Tamil Nadu to 2.6 in Meghalaya). Presently, two prominent regions in the country exhibit high obesity rates: the southern region, including Tamil Nadu (29%), Kerala (25%), Goa (25%), and Andhra Pradesh (23%), and the northwestern region, encompassing Delhi (33%), Punjab (31%), and Haryana (24%). Moreover, the disparity in obesity rates across states has widened over time, with states initially showing higher rates experiencing a faster growth rate compared to those with lower initial rates, as highlighted by the β- and σ-convergence analyses. There was substantial variation in obesity rates across education, wealth, place of residence, and social group categories. The risk of obesity is higher among older, educated, wealthy, non-Hindu EMWRAs and TV watchers, but lower among those living in rural areas, the southern region, smaller households, and belonging to SC, ST, and OBC social groups. Conclusion The surge in obesity among Indian ever married women of reproductive age calls for immediate public health measures. Customized strategies, acknowledging regional differences, are vital to tackle diverse obesity rates across states. Prioritizing vulnerable groups, including the poor, uneducated, and urban populations, is critical for ensuring fair health outcomes.